What Types of Codes are Mixed in Indonesia?: An Investigation of Code Mixing in a Magazine - Zulfadli A. Aziz; Diana Achmad; Maizura Fadlun (English Education Journal, 2019)
Mass media have been regarded as playing crucial roles in introducing and promoting foreign terms into Indonesian. It can be seen that many magazines have been mostly influenced by English through code mixing to make the writing become more prestigious and cool. This present study aims at investigating the types of code mixing used in a magazine. It employs the three types of code mixing, proposed by Musyken’s (2000), which are: insertion, alternation, and congruent lexicalization. The data were taken from Aplaus magazine in four editions from April to July 2016 on the Journey Section. In collecting the data, the occurrence of English code mixing in one of the sections in the magazine was noted, and the data were then classified and tabulated. The results of this research show that not all of three types of code mixing by Musyken (2000) were applicable in the Aplaus magazine. There are 36 insertion types found or about 76.6%, 11 or about 23.4% for alternation, and no case of congruent lexicalization appeared. Thus, the dominant type of code mixing used in the magazine was insertion.